The usefulness of the debate between focus on form and focus on forms (BRAC University Journal, 2026)
The literature review includes 13 articles and 2 chapters from 2 books titled Handbook of Research in Second Language Teaching, and Learning, and Approaches and Methods in Language Teaching published in the last ten years focusing on the efficacy of Focus on form (FonF) or the communicative use of grammar in comparison with Focus on forms (FonFS) or the explicit use of grammar in language classrooms. The first section discusses researchers’ views on the employment of FonF vs. FonFS addressing issues like when FonF arises, points in favor of and against FonF in relation to FonFS, and different variables affecting the success of FonF. The second section discusses different views of learners regarding classroom use of FonF and FonFS with a separate subsection on the views held by the US and Colombian FL learners as they represent two contrasting preferences in terms of the adoption of FonF and FonFS. The third and final section deals with teachers’ views regarding the efficacy of FonF and FonFS followed by the difference in view among the US and Colombian FL teachers and how FonFS can be synthesized into FonF. The findings reveal that there is no universal efficacy of either FonF or FonFS; it is rather the context which decides on the efficacy of these two. Moreover, it is to be noted that a choice between FonF or FonFS is not mutually exclusive and one can be incorporated into the other.